Humanistic Values For Children In Ben Stassen's Sammy's Adventures Movie (2010): A Sociological Approach - Prastyo, Roqib (2012)
This study is aimed to show Humanisticvalues for children in Ben Stassen's Sammy's Adventures movie by using sociological approach. It is done by establishing two objectives: the first is analyzing the movie based on structural elements of the movie and the second is analyzing the movie based on the sociological approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is Sammy's Adventuresmovie directed by Ben Stassen released in 2010. While the secondary data sources are other materials taken from books, encyclopedia, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. Firstly, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise-en scene, cinematography, sound and editing are related to each other and form the unity into good quality movie, secondly, based on the sociological analysis, there is a close relationship between the movie story and the reality conditional of American society that have humanistic values for children. It is reflected by the characters in the movie. This movie directed the behavior of character that reflected in the scene. This story employs many techniques in order to persuade its audience into believing.